已知函数f(x)对任意x∈R都有f(x)+f(1-x)=
(1)求f(
(2)若数列{an}满足an=f(0)+f(
(3)设bn=
|
(1)在f(x)+f(1-x)=
中,1 2
令x=
,可得f(1 2
)+f(1 2
)=1 2
,所以f(1 2
)=1 2 1 4
令x=
,可得f(1 n
)+f(1 n
)=n-1 n 1 2
(2)an=f(0)+f(
)+f(1 n
)+…+f(2 n
)+f(1),又可以写成n-1 n
an=f(1)+f(
)+f(n-1 n
)+…+f(n-2 n
)+f(0),1 n
两式相加得,2an=[f(0)+f(1)]+[f(
)+f(1 n
)]+…[f(1)+f(0)]n-1 n
=(n+1)[f(0)+f(1)]=n+1 2
∴an=n+1 4
(3)bn=
=4 4an-1
,cn=bnbn+1=4 n
•4 n
=16(4 n+1
-1 n
)1 n+1
∴Tn=16[(
-1 1
)+(1 2
-1 2
)+…+(1 3
-1 n
)+(1 n+1
-1 2
)+…+(1 3
-1 n
)]=16(1-1 n+1
)=1 n+1 16n n+1